A critical role for Arabidopsis MILDEW RESISTANCE LOCUS O2 in systemic acquired resistance. (10th May 2018) - Gruner, Katrin; Zeier, Tatyana; Aretz, Christina; Zeier, Jürgen
Summary: Members of the MILDEW RESISTANCE LOCUS O ( MLO) gene family confer susceptibility to powdery mildews in different plant species, and their existence therefore seems to be disadvantageous for the plant. We recognized that expression of the Arabidopsis MLO2 gene is induced after inoculation with the bacterial pathogen Pseudomonas syringae, promoted by salicylic acid (SA) signaling, and systemically enhanced in the foliage of plants exhibiting systemic acquired resistance (SAR). Importantly, distinct mlo2 mutant lines were unable to systemically increase resistance to bacterial infection after inoculation with P. syringae, indicating that the function of MLO2 is necessary for biologically induced SAR in Arabidopsis. Our data also suggest that the close homolog MLO6 has a supportive but less critical role in SAR. In contrast to SAR, basal resistance to bacterial infection was not affected in mlo2 . Remarkably, SAR‐defective mlo2 mutants were still competent in systemically increasing the levels of the SAR‐activating metabolites pipecolic acid (Pip) and SA after inoculation, and to enhance SAR‐related gene expression in distal plant parts. Furthermore, although MLO2 was not required for SA‐ or Pip‐inducible defense gene expression, it was essential for the proper induction of disease resistance by both SAR signals. We conclude that MLO2 acts as a critical downstream component in the execution of SAR to bacterial infection, being required for the translation of elevated defense responses into disease resistance. Moreover, our data suggest a function for MLO2 in the activation of plant defense priming during challenge by P. syringae . Significance Statement: MILDEW RESISTANCE LOCUS O genes are known as susceptibility factors to powdery mildew infection. The present results indicate that Arabidopsis MLO2 is necessary for the execution of plant systemic acquired resistance to bacterial pathogen challenge at a very downstream position in the SAR‐regulatory network.